Physicochemical and sensory characteristics of meat from lambs fed diets containing mulberry hay - Alves Cirne, Luis Gabriel; Silva Sobrinho, Americo Garcia da [UNESP]; Oliveira, Emanuel Almeida de [UNESP]; Jardim, Rodrigo Desessards; Varela Junior, Antonio Sergio; Pinto de Carvalho, Gleidson Giordano; Luz Jaeger, Soraya Maria Palma; Bagaldo, Adriana Regina; Almeida, Fabiana Alves de [UNESP]; Endo, Viviane [UNESP]; Bezerra Moreno, Greicy Mitzi; Valenca, Roberta de Lima [UNESP] (Taylor & Francis Ltd, 2018)
The aim of this study was to evaluate the physicochemical and sensory characteristics of the of meat lamb fed diets containing 0%, 12.5%, and 25.0% mulberry hay (total diet). Twenty-four ile-de-France lambs in the feedlot at an average age of 60 days and 15 kg body weight were allocated to individual stalls and slaughtered at 32 kg BW. Mulberry hay inclusion in the diet did not affect the meat pH 45 min (6.45) and 24h (5.70) after slaughter. Average luminosity (L*), red intensity (a*), and yellow intensity (b*) values in the meat 24h after slaughter were 40.85, 14.51, and 4.17, respectively. No differences were observed for water-holding capacity (58.03%), cooking loss (41.95%), shear force (2.80 kgf/cm(2)), sarcomere length (1.60 mu m), or the sensory traits appearance (7.29), taste (7.23), tenderness (7.51), and overall acceptance (7.48). Inclusion of up to 25% mulberry hay in a concentrate-based diet did not compromise the physicochemical and sensory traits of the meat, indicating that this ingredient is as a good alternative to provide nutrients in the diet of feedlot lambs.
Keywords: Feedlot; meat colour; softness; cooking losses; meat flavour